Bayesian Learning and Gender Segregation - Breen, Richard; García‐Peñalosa, Cecilia (Journal of Labor Economics, 2002)
We present an explanation for the persistence of gender segregation in occupations and for the observed cross‐country differences in its extent. Agents have imperfect information about their probability of success in different occupations and base their career choices on prior beliefs about these probabilities. Beliefs are updated according to Bayes's rule, implying that past differences in preferences over occupations across genders affect the beliefs of the current generation. Consequently, even when men and women become identical in their preferences, their career choices differ. Moreover, the way in which preferences change is shown to affect the degree of segregation.